Behavioral and pharmacological modulation of respiration in rhesus monkeys. - Howell, L L (1994)
Changes in respiration associated with schedule-controlled behavior were determined in seated rhesus monkeys prepared with a pressure-displacement head plethysmograph for monitoring ventilation continuously during behavioral experiments. Subjects were trained to press a lever under fixed-ratio 40 and fixed-interval 300-s schedules of stimulus termination. Episodic increases in ventilation were closely associated with periods of responding under both schedules. Recurring episodes of increased ventilation occurred during fixed-ratio responding, and were separated by brief 10-s timeouts during which ventilation decreased. Under the fixed-interval schedule, both ventilation and response rate typically increased as the 300-s interval elapsed. The effects of cocaine, caffeine, and two adenosine agonists, 5'-N-ethylcarboxamidadenosine (NECA) and 2-(carboxyethylphenylamino)adenosine-5'-carboxamide (CGS 21680), on behavior and respiration were determined using a cumulative-dosing procedure. Drug-induced suppression of behavior eliminated the episodic increases in ventilation during the performance components of both schedules. Schedule-related increases in ventilation were compared to those produced by elevated levels of CO2 in inspired air. Exposure to 4% CO2 mixed in air increased ventilation in all subjects, and the combined effects of CO2 exposure and schedule-controlled responding on respiration appeared to be additive. The results suggest that behavioral activities may increase ventilation through increased metabolic demand and increased CO2 production.